Biofungicides derived from indigenous microorganisms fermented on Tagetes erecta L. flowers for the control of anthracnose in chili pepper (Capsicum annuum L.) - Ambardini, Sri; Yanti, Nur Arfa; Mamangkey, Jendri; Arsyat, Elvina Yustika; Ardiansyah (Plant Science Today, 2025)
Local microorganisms (LMo) are native microbial consortia that colonize specific substrates and ferment them when supplemented with nutrients. LMo-based products are emerging as eco-friendly alternatives for plant disease management. In this study, Tagetes erecta L. flowers were used as a substrate to cultivate LMo, which were then cross-applied to chili peppers (Capsicum annuum L.) to control anthracnose disease caused by Colletotrichum capsici. The research aimed to evaluate the antifungal activity, minimum fungicidal concentration (MFC) and overall effectiveness of LMo derived from T. erecta flowers against C. capsici. The study was conducted in 3 stages: first, assessing the antifungal activity of LMo using the agar dilution method, second, determining the MFC of the LMo solution and third, evaluating the in planta efficacy of LMo in controlling anthracnose. Results demonstrated that LMo formulated from T. erecta exhibited strong antifungal activity, with a 15.99 mm inhibition zone and an MFC of 40%. In the field trial, a 50% LMo concentration significantly suppressed anthracnose, improving chili pepper condition and appearance compared to both negative and positive controls. These findings suggest that LMo based on T. erecta flowers offers a cost-effective, abundant and eco-friendly solution for anthracnose management, particularly for chili farmers in Southern Sulawesi.